Early postoperative albumin level following total knee arthroplasty is associated with acute kidney injury: A retrospective analysis of 1309 consecutive patients based on kidney disease improving global outcomes criteria. Issue 31 (August 2016) - Kim, Ha-Jung; Koh, Won-Uk; Kim, Sae-Gyeol; Park, Hyeok-Seong; Song, Jun-Gol; Ro, Young-Jin; Yang, Hong-Seuk
Abstract : Abstract: Hypoalbuminemia has been reported to be an independent risk factor for acute kidney injury (AKI). However, little is known about the relationship between the albumin level and the incidence of AKI in patients undergoing total knee arthroplasty (TKA). The aim of our study was to assess incidence and risk factors for AKI and to evaluate the relationship between albumin level and AKI following TKA. The study included a retrospective review of medical records of 1309 consecutive patients who underwent TKA between January 2008 and December 2014. The patients were divided into 2 groups according to the lowest serum albumin level within 2 postoperative days (POD2_alb level < 3.0 g/dL vs ≥3.0 g/dL). Multivariate logistic regression analysis was used to assess risk factors for AKI. A comparison of incidence of AKI, hospital stay, and overall mortality in the 2 groups was performed using propensity score analysis. Of 1309 patients, 57 (4.4%) developed AKI based on Kidney Disease Improving Global Outcomes criteria. Factors associated with AKI included age (odds ratio [OR] 1.05; 95% confidence interval [CI] 1.01–1.09; P  = 0.030), diabetes (OR 3.12; 95% CI 1.65–5.89; P  < 0.001), uric acid (OR 1.51; 95% CI 1.26–1.82; P  < 0.001), beta blocker use (OR 2.65; 95% CI 1.48–4.73; P  = 0.001), diuretics (OR 16.42; 95% CI 3.08–87.68; P  = 0.001), and POD2_alb level < 3.0 g/dL (OR 1.92; 95% CI 1.09–3.37; P  = 0.023). After propensity score analysis, POD2_alb level<3.0 g/dL was associated with AKI occurrence (OR 1.82; 95% CI 1.03–3.24, P  = 0.041) and longer hospital stay ( P  = 0.001). In this study, we demonstrated that POD2_alb level<3.0 g/dL was an independent risk factor for AKI and lengthened hospital stay in patients undergoing TKA.